Nanocarrier mediated autophagy: An emerging trend for cancer therapy. (October 2021) - Singh, Ajit; Handa, Mayank; Ruwali, Munindra; Flora, S.J.S; Shukla, Rahul; Kesharwani, Prashant
Highlights: Autophagic pathway interaction with nanocarriers causes autophagy inhibition. Nanocarriers have application in anticancer delivery agents to cancer cells. The review covers nanoparticles mediated autophagy modulation. Abstract: Autophagy is defined as a process in which cell undergo sequential sequestration of degraded protein and damaged organelles for maintenance of cellular hemostasis. Autophagy is regulated by complex mammalian target of rapamycin complex 1 (m-TORC) pathway, and its types depends on nature phagocytized material. Interaction of autophagic signaling pathway with nanocarriers causes autophagy inhibition and cell death. The role different classes of nanomaterials in autophagy perturbation, both regulation and inhibition in in-vitro and animal models were studied. These nanocarriers have application in anticancer delivery agents to cancer cells. Due to retention of NPs in mitochondria and endoplasmic reticulum induces stress and up-regulates autophagy sequences. This co-localization of NPs in organelles lead to cancer cell death due to autophagy inhibition. The review covers autophagy regulation pathways and NPs mediated autophagy modulation in combination with chemotherapeutics has been explored for cancer therapy with their toxicity concerns.